1998
DOI: 10.1007/bf01782894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two different concepts of lumbar posterior osteosynthesis implants A finite-element analysis

Abstract: Summary: The present study is a numerical comparison using finite-element analysis (FEA) oftwo different concepts of spinal fixation devices when implanted. These implants are 1) the Easy ®, "rigid" Screw/Rod (0 6mm) system; z) the Twinflex ®, "dynamic" system (o 2 x 2.5 mm ELF). A parameterised 3D FEA model of an L3-sacrum segment, developed by Lavaste, Skalli & Robin, was used. Geometric and mechanical models of each implant were then constructed, before being inserted in the spinal segment model. Then, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The authors found that the dynamic system enabled more load to be transferred through the anterior column and the interbody graft, as compared with rigid instrumentation, without compromising stability. 33 These findings confirmed those reported by Templier et al 22 in 1998, suggesting that a dynamic device (Twinflex) could offer a more favorable environment for enhanced interbody fusion healing ( Figure 4 ). Reducing the flexural rigidity of lumbar fixation results in more homogeneous load transmission along the system without reducing the rigidity of the whole system.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The authors found that the dynamic system enabled more load to be transferred through the anterior column and the interbody graft, as compared with rigid instrumentation, without compromising stability. 33 These findings confirmed those reported by Templier et al 22 in 1998, suggesting that a dynamic device (Twinflex) could offer a more favorable environment for enhanced interbody fusion healing ( Figure 4 ). Reducing the flexural rigidity of lumbar fixation results in more homogeneous load transmission along the system without reducing the rigidity of the whole system.…”
Section: Discussionsupporting
confidence: 86%
“…Templier et al 22 evaluated the role of the longitudinal component in load transfer between the FSU and implant via finite element analysis (FEA) ( Table 4 ). Using a 3D geometric FE L3-sacrum model, the authors compared load transmission of rigid instrumentation versus the semirigid Twinflex system ( Figure 3 ) following the application of a flexion moment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggested that eliminating mechanical loads on an interbody bone graft may result in negative bone remodeling, pseudarthrosis, and osteoporosis [ 3 6 ]. This “stress shielding” phenomenon at the disk space level may result from the excessive stiffness of traditional rigid instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Templier et al [ 6 ] using a 3D geometric FE model of the lumbar spine postulated that the TWINFLEX semirigid device could offer a more favorable biomechanical environment for enhanced interbody fusion healing. They evaluated the role of the longitudinal component in load transfer between the FSU and implant and noted that by reducing the stiffness of lumbar fixation, there was more homogeneous load transmission throughout the FSU without significantly reducing the rigidity of the instrumented spinal segment.…”
Section: Introductionmentioning
confidence: 99%